2002
DOI: 10.1016/s1097-2765(02)00568-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Tuberous Sclerosis Complex-2 Tumor Suppressor Gene Product Tuberin as a Target of the Phosphoinositide 3-Kinase/Akt Pathway

Abstract: The S/T-protein kinases activated by phosphoinositide 3-kinase (PI3K) regulate a myriad of cellular processes. Here, we show that an approach using a combination of biochemistry and bioinformatics can identify substrates of these kinases. This approach identifies the tuberous sclerosis complex-2 gene product, tuberin, as a potential target of Akt/PKB. We demonstrate that, upon activation of PI3K, tuberin is phosphorylated on consensus recognition sites for PI3K-dependent S/T kinases. Moreover, Akt/PKB can phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

30
1,073
6
11

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,379 publications
(1,134 citation statements)
references
References 51 publications
30
1,073
6
11
Order By: Relevance
“…mTOR phosphorylates p70S6K on Thr389, which correlates with activation of p70S6K (Dufner and Thomas, 1999;Li et al, 2003;Pan et al, 2004). In agreement with the postulated cascade described above, it was found that overexpression of tuberin suppresses phosphorylation of p70S6K on residue Thr389 (representing S6K activity) (Dan et al, 2002;Goncharova et al, 2002;Inoki et al, 2002;Manning et al, 2002;Potter et al, 2002;Tee et al, 2002). In addition, ERK-mediated phosphorylation of tuberin on Ser664 negatively regulates tuberin's function by blocking its interaction with hamartin.…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…mTOR phosphorylates p70S6K on Thr389, which correlates with activation of p70S6K (Dufner and Thomas, 1999;Li et al, 2003;Pan et al, 2004). In agreement with the postulated cascade described above, it was found that overexpression of tuberin suppresses phosphorylation of p70S6K on residue Thr389 (representing S6K activity) (Dan et al, 2002;Goncharova et al, 2002;Inoki et al, 2002;Manning et al, 2002;Potter et al, 2002;Tee et al, 2002). In addition, ERK-mediated phosphorylation of tuberin on Ser664 negatively regulates tuberin's function by blocking its interaction with hamartin.…”
Section: Introductionsupporting
confidence: 55%
“…Ras regulates Raf upstream of MEK/ERK/RSK. Both, ERK-mediated phosphorylation of tuberin and RSK-dependent phosphorylation of tuberin, inhibit its potential to block mTOR/p70S6K (Dan et al, 2002;Inoki et al, 2002;Manning et al, 2002;Potter et al, 2002;Roux et al, 2004;Ballif et al, 2005;Ma et al, 2005). Since Ras regulates different pathways, it is likely that the selection of distinct effectors can lead to different outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous downstream effectors of Akt/PKB have been described, among many others forkhead transcription factors, GSK3b, Bad and the cell cycle inhibitor p27 KIP1 (Brazil et al, 2004). In addition, Akt/PKB is able to phosphorylate TSC2, inhibiting the TSC complex and thereby indirectly stimulating growth (Dan et al, 2002;Manning et al, 2002;Potter et al, 2002). The physiological significance of this modification in Drosophila is not clear, as dTSC2 mutant flies expressing engineered TSC2 constructs where the PKB phosphorylation sites (Ser924 and Thr1518) were mutated to nonphosphorylatable alanine-or phospho-mimicking aspartate/glutamate residues completely rescued lethality of TSC2 mutants (Dong and Pan, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In mammalian cells, mTOR signalling depends on signal transmission through the phosphoinositide 3-kinase (PI3K)/Akt pathway. Activated Akt phosphorylates TSC2, a component of tuberous sclerosis complexes 1 and 2, sensitive to nutrient status, and favours mTOR activity (Manning et al, 2002;Zhang et al, 2003). An important function of mTOR is the translation control via activation of ribosomal p70S6 kinase (S6K1) and suppression of 4E-BPs, resulting in enhanced translation of mRNAs encoding cell-cycle regulators and promotion of G1 -S cell-cycle transition (Schmelzle and Hall, 2000;Bjornsti and Houghton, 2004).…”
mentioning
confidence: 99%